Answer:
tan A + tan B + tan C = tan A tan B tan C
Explanation:
Explanation:-
proof:-
Given A B and C are angles of an oblique, non-right, triangle
we know that A+B+C = 180
A+B = 180 - C
Apply ' tan' on both sides , we get
Tan(A+B) = Tan ( 180 - C)
![(tan A+ tan B)/(1-tanA tan B) = tan( 180 -C)](https://img.qammunity.org/2021/formulas/mathematics/college/qqammeow9dssmzbznl08zohkbk9doghkto.png)
tan A + tan B = - tan(180- C) ( 1 - tan A tan B )
tan A + tan B = - tan C ( 1 - tan A tan B )
tan A + tan B = - tan C + tan A tan B tan C
tan A + tan B + tan C = tan A tan B tan C